Mouse Models for Cytomegalovirus Infections in Newborns and Adults. Issue 9 (9th September 2022) - Brizić, Ilija; Lisnić, Berislav; Krstanović, Fran; Brune, Wolfram; Hengel, Hartmut; Jonjić, Stipan
Abstract: This article describes procedures for infecting adult mice with murine cytomegalovirus (MCMV) and for infecting newborn mice to model congenital CMV infection. Methods are included for propagating MCMV in cell cultures and preparing a more virulent form of MCMV from the salivary glands of infected mice. A plaque assay is provided for determining MCMV titers of infected tissues or virus stocks. Also, methods are described for preparing the murine embryonic fibroblasts used for propagating MCMV, and for the plaque assay. © 2022 Wiley Periodicals LLC.